Kelas Motivasi untuk Menghadapi Seleksi Calon Aparatur Sipil Negara Formasi Dosen Tahun 2023 - Pongtambing, Yulita Sirinti; Admawati, Harsi; Anggraini, Asterina; Andayani, Qurnia; Delyarahmi, Sucy; Putra, Nararia Hutama; Manapa, Esther S; Novitasari, Ani (Institut Nalanda, 2023)
In 2023, the selection of Civil Servant Candidates for lecturer formation was opened by the Indonesian government. Thorough preparation for applicants is needed. One of the necessary preparations is mental preparation. Based on the candidates’ mental preparation, this community service aimed to increase their motivation. Furthermore, the activity was conducted through the Focus Group Discussion (FGD) method via Zoom meeting. The motivation material was delivered by four experienced civil servant lecturers participating in the selection in 2021, and it was guided by another lecturer as the moderator. Moreover, there were 88 attending participants with an average of 75 participants. The participants were involved in interactive discussions after the material presentation session. Based on the presentation and discussion, communicating with immediate family, focusing on completing documents for administrative selection, following related information and regulations actively, and preparing mentally are essential things to face in the selection of Civil Servant Candidates for lecturer formation.